PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL INTERAKTIF ALAM PEMBELAJARAN IPA BERBASIS ANIMAKER UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI UPT SPF SMPN 21 MAKASSAR - Muhrida Jalil; Andi Syukri Syamsuri; Syarifuddin,Cn Sida (STKIP Subang, 2024)
This study aims to evaluate the of using nteractive digital learning media based on Animaker in improving students' learning outcomes in science subjects at UPT SPF SMPN 21 Makassar. The background of this research is the lack of variety in the learning media used by teachers, which causes student boredom and negatively impacts their learning outcomes. This research employs a quantitative method with a one-group pretest-posttest design. The study population consists of 272 students spread across 7 classes, with a purposive sample of class VIII G comprising 28 students. The research instruments used include interviews and tests, while data analysis is conducted using statistical techniques such as pretest, posttest, normality test, homogeneity test, and t-test, processed through SPSS version 29. The results show a significant improvement in students' learning outcomes after using Animaker-based learning media, where the t-test value is greater than the t-table, thus accepting both H0 and Hi. Therefore, it can be concluded that the use of Animaker-based interactive digital learning media is effective in enhancing the science learning outcomes of class VIII G students at UPT SPF SMPN 21 Makassar.